PENERAPAN METODE LOK-R UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI BELAJAR PESERTA DIDIK MATA PELAJARAN PAI - Iva Imroatus Sholihah; Zuhriyyah Hidayati; Abu Amar (Rihlah Review: Jurnal Pendidikan Islam, 2024)
Effective communication in the learning process is essential to improve material understanding and student engagement. To improve these skills, teachers try to learn through the LOK-R (Literacy, Orientation, Collaboration, and Reflection) method. This study aims to determine the application of the LOK-R method in SMP Negeri 1 Modo in PAI subjects. This study uses a qualitative method with a case study approach. The subject of the study was a grade VII student at SMP Negeri 1 Modo, who was chosen purposively. Data collection is carried out through observation, in-depth interviews, and document analysis. The data obtained were analyzed by thematic analysis techniques to identify patterns and themes related to student learning communication. The results of the study show that the application of the LOK-R learning method includes processes such as literacy, orientation, collaboration and also reflection. The impact of the application of the LOK-R method is effective in improving students' communication skills. There was an increase in students' active participation in class discussions and presentations. Students are more confident in expressing opinions and are able to communicate better. In addition, through reflection, students can identify their weaknesses and strengths in communicating, as well as make continuous improvements.